2007
DOI: 10.1007/s00442-007-0886-9
|View full text |Cite
|
Sign up to set email alerts
|

Experimental support for the cost–benefit model of lizard thermoregulation: the effects of predation risk and food supply

Abstract: Huey and Slatkin's (Q Rev Biol 51:363-384, 1976) cost-benefit model of lizard thermoregulation predicts variation in thermoregulatory strategies (from active thermoregulation to thermoconformity) with respect to the costs and benefits of the thermoregulatory behaviour and the thermal quality of the environment. Although this framework has been widely employed in correlative field studies, experimental tests aiming to evaluate the model are scarce. We conducted laboratory experiments to see whether the common l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 61 publications
1
50
0
3
Order By: Relevance
“…This result reflects behavioural buffering, where cool-treatment snakes emerged to bask earlier in the day, and kept basking for longer as well as closer to the heating lamp (F. A., personal observation). Comparable buffering behaviour has been described in lizards where sub-optimal temperatures led to longer basking periods -but these lizards often foraged at sub-optimal temperature with lower sprint speeds and predatory efficiency (Bennett, 1980;Christian and Tracy, 1981;Avery et al, 1982;Herczeg et al, 2008). In our study, bodytemperature regimes were unaffected by our experimental manipulations (at least outside of feeding periods); thus, showing that lower growth rates [as also seen in lizards kept at unfavourable thermal regimes (Avery, 1984;Sinervo and Adolph, 1994;Martin and Lopez, 1999)] may be elicited by ambient thermal challenges even if body-temperatures are unaffected.…”
Section: Discussionmentioning
confidence: 93%
“…This result reflects behavioural buffering, where cool-treatment snakes emerged to bask earlier in the day, and kept basking for longer as well as closer to the heating lamp (F. A., personal observation). Comparable buffering behaviour has been described in lizards where sub-optimal temperatures led to longer basking periods -but these lizards often foraged at sub-optimal temperature with lower sprint speeds and predatory efficiency (Bennett, 1980;Christian and Tracy, 1981;Avery et al, 1982;Herczeg et al, 2008). In our study, bodytemperature regimes were unaffected by our experimental manipulations (at least outside of feeding periods); thus, showing that lower growth rates [as also seen in lizards kept at unfavourable thermal regimes (Avery, 1984;Sinervo and Adolph, 1994;Martin and Lopez, 1999)] may be elicited by ambient thermal challenges even if body-temperatures are unaffected.…”
Section: Discussionmentioning
confidence: 93%
“…It has to be noted that we did not try to test the cost-beneWt model of thermoregulation proposed by Huey and Slatkin (1976) which predicts that an ectotherm should stop thermoregulating when the costs of thermoregulation outweigh the beneWts. Although the model has been considered extensively in the past 10 years (Blouin-Demers and Weatherhead 2001;Blouin-Demers and Nadeau 2005;Herczeg et al 2006Herczeg et al , 2008, estimating the costs and beneWts of thermoregulation is diYcult as it requires knowledge of the costs of energy expenditure (based on the frequency distribution and the spatial distribution of T e ), the costs associated with missed opportunities and predation risks, as well as the interaction between these costs (Angilletta 2009). Furthermore, the quality of the three thermal treatments we oVered to tuatara did not diVer in their thermal quality (d e was the same in all three treatments) but in the length of time that T sel was available; therefore, we manipulated thermal constraint rather than energetic cost.…”
Section: Discussionmentioning
confidence: 99%
“…At birth, juveniles born to mothers exposed to predator cues also selected lower temperatures, reflecting a diminution in basking behaviour (less time spent in the hottest part of the temperature gradient). Previous studies found that when in the presence of predator cues, common lizards reduce their basking behaviour [31,60,61], presumably because lizards are particularly vulnerable to predation while basking in the open. Our study adds to these findings by demonstrating that maternal exposure to predator cues during gestation is sufficient to trigger a change in juvenile thermoregulation behaviour even in the absence of actual predation stimulus in the natal environment.…”
Section: Discussionmentioning
confidence: 99%